Gambaran Kinerja Pengomposan Limbah Padat Rumah Potong Hewan Tamangapa Kota Makassar dengan Sistem Aerasi Pasif - Hartono .; St. Fatma Hiola; Surahman Nur; Oslan Jumadi (Fakultas MIPA UNM, 2021)
Abstract. Slaughterhouse waste is generally disposed into the environment without being processed, so that it potentially causes air pollution, water pollution, and soil pollution. Slaughterhouse waste can be processed and used as plant fertilizer through the composting process. This study aims to compare the composting performance of solid waste at Tamangapa RPH Makassar between the main ingredient consisting of rumen contents only (treatment I) with that consisting of a mixture of rumen contents with livestock manure (treatment II). We recorded quantitative data including temperature (0C), pH, material mass reduction and composting time and qualitative parameters including color, smell and texture of the resulting compost. The composting process was carried out in a compost box with a size of 40x40x60 cm with a passive aeration system for 4 weeks with three replications. Our results demonstrated that treatment I and treatment II had a similar pattern of temperature changes, while the average pH of treatment I was higher compared to treatment II. Based on the composting performance data including changes in temperature and pH from the first week to the fourth week of composting, we concluded that both treatments resulted in a rapid composting process with good-quality compost.Keywords: composting performance, RPH solid waste, composting process, rumen contents, passive aeration.